Nudging private Ryan: mobile microgiving under economic incentives and audience effects - Lee, Dongwon (2024)
Technology-augmented choice-making impacts many facets of business. The use of economic incentives under the ubiquitous mobile ecosystem for prosocial behavior has been shown to be particularly effective. We build on the previous work on this topic and study how mobile-based economic incentives and environments influence charitable giving behavior. In contrast to traditional fund-raising, we consider the use of mobile devices to generate giving in small denominations, which we term microgiving. In collaboration with a US-based mobile app provider, we incorporated a functionality that allowed users to contribute their in-app reward points to charity. To encourage donations, we used economic incentives in the form of monetary subsidies, i.e., rebates or matching grants, as well as digital nudges in the form of push notifications. We studied the effects of these factors on giving behavior across two large-scale field experiments. Focusing on the different aspects of smartphones that could differentially impact charitable giving behavior—namely the intensely private and personal nature of smartphones—we examined how the visibility of donation decisions affects giving behavior by toggling audience effects. Our results show that the effectiveness of incentives is contingent upon the magnitude of the incentive as well as the extent to which individual decisions are visible to others. To situate our results in relation to the traditional medium of charitable giving, we propose an analytical model that internalizes the subsidy rates and the audience effect. This study provides initial empirical evidence and an analytical model to advance technology-augmented charitable giving that can provide insights to organizations and service providers.